A Reappraisal on the Potential Ability of Human Neutrophils to Express and Produce IL-17 Family Members In Vitro: Failure to Reproducibly Detect It - Tamassia, Nicola; Arruda-Silva, Fabio; Calzetti, Federica; Lonardi, Silvia; Gasperini, Sara; Gardiman, Elisa; Bianchetto-Aguilera, Francisco; Gatta, Luisa Benerini; Girolomoni, Giampiero; Mantovani, Alberto; Vermi, William; Cassatella, Marco A. (Frontiers in Immunology, 2018)
Neutrophils are known to perform a series of effector functions that are crucial for the innate and adaptive responses, including the synthesis and secretion of a variety of cytokines. In light of the controversial data in the literature, the main objective of this study was to more in-depth re-evaluate the capacity of human neutrophils to express and produce cytokines of the IL-17 family in vitro. By RT-qPCR, protein measurement via commercial ELISA, immunohistochemistry (IHC) and immunofluorescence (IF), flow cytometry, immunoblotting, chromatin immunoprecipitation and ChIP-seq experiments, we found that highly pure (> 99.7 %) populations of human neutrophils do not express/produce IL-17A, IL-17F, IL-17AF or IL-17B mRNA/protein upon incubation with a variety of agonists. Similar findings were observed by analyzing neutrophils isolated from active psoriatic patients. In contrast with published studies, IL-17A and IL-17F mRNA expression/production was not even found when neutrophils were incubated with extremely high concentrations of IL-6 plus IL-23, regardless of their combination with inactivated hyphae or conidia from Aspergillus fumigatus. Consistently, no deposition of histone marks for active (H3K27Ac) and poised (H3K4me1) genomic regulatory elements was detected at the IL-17A and IL-17F locus of resting and IL-6 plus IL-23-stimulated neutrophils, indicating a closed chromatin conformation. Concurrent experiments revealed that some commercial anti-IL-17A and anti-IL-17B antibodies, although staining neutrophils either spotted on cytospin slides or present in inflamed tissue samples by IHC/IF, do not recognize intracellular protein having the molecular weight corresponding to IL-17A or IL-17B, respectively, in immunoblotting experiments of whole neutrophil lysates. By contrast, the same antibodies were found to more specifically recognize other intracellular proteins of neutrophils, suggesting that their ability to positively stain neutrophils in cytospin preparations or tissue samples derives from IL-17A- or IL-17B-independent detections. In sum, our data confirm and extend, also at epigenetic level, previous findings on the incapability of highly purified populations of human neutrophils to express/produce IL-17A, IL-17B and IL-17F mRNAs/proteins in vitro, at least under the experimental conditions herein tested. Data also provide a number of justifications explaining, in part, why it is possible to false positively detect IL-17A+-neutrophils.